2018
DOI: 10.1093/ndt/gfy147
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and control of hypertension by 48-h ambulatory blood pressure monitoring in haemodialysis patients: a study by the European Cardiovascular and Renal Medicine (EURECA-m) working group of the ERA-EDTA

Abstract: Abstract Background Population-specific consensus documents recommend that the diagnosis of hypertension in haemodialysis patients be based on 48-h ambulatory blood pressure (ABP) monitoring. However, until now there is just one study in the USA on the prevalence of hypertension in haemodialysis patients by 44-h recordings. Since there is a knowledge gap on the problem in European countries, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…In patients with end-stage-renal-disease (ESRD) undergoing hemodialysis, the prevalence of hypertension is estimated at 70-90% [1,2]. During hemodialysis blood pressure (BP) levels vary.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with end-stage-renal-disease (ESRD) undergoing hemodialysis, the prevalence of hypertension is estimated at 70-90% [1,2]. During hemodialysis blood pressure (BP) levels vary.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey that included 160 U.S. practicing nephrologists found that the highest percentage of respondents prescribe CCAs (68%) because they consider it to be more effective in treating hypertension in dialysis patients, followed by BB (35%), ACE (32%), BRA (29%), and diuretics (25%) . Studies suggest that lower systolic and diastolic blood pressure with the use of antihypertensive drugs results in a 30% lower risk of cardiovascular events and mortality, but adequately controlled hypertension is observed in only 65% of hypertensive patients …”
Section: Discussionmentioning
confidence: 99%
“…Elevated blood pressure (BP) is highly prevalent in the dialysis population affecting more than 80% of patients and is a risk factor for cardiovascular outcomes, including ventricular hypertrophy, cardiac insufficiency, and cardiovascular events …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus volume overload is currently considered the main pathogenic mechanism of hypertension in the ESRD population [ 5 ]. As a matter of fact, the worldwide prevalence of hypertension in this population is as high as 85% [ 40 ]. The increase in volume during the interdialytic intervals likely contributes to short-term BP variability from Day 1 to Day 2 of the regular interdialytic interval [ 41 ], which has been implicated in the risk for cardiovascular events independent of BP levels [ 42 ].…”
Section: Introductionmentioning
confidence: 99%